1 Corinthians - Johnson, Alan F. (Leicester : Inter-Varsity, 2004)
"Upwardly mobile Christians facing radically diverse ethnic, religious, economic and social conditions. The church divided over issues of leadership and authority, sexual morality, gender and worship, marriage and divorce. Sound familiar? First-century Corinth and its challenges were not so different from our own. Yet in the midst of this detailed, practical letter to a church in crisis is found one of the greatest paeans to love ever written. And, of course, love is just what is needed to address these complex human issues whether in the first century or the twenty-first.".
"In this analysis of 1 Corinthians, readers will find an introduction that discusses the social, cultural and historical background of the city and its people. Rounding out the introduction are explorations of the letter's occasion and date, authorship and purpose, and major theological themes. Passage-by-passage commentary follows that seeks to explain what the letter means for us today as well as what it meant for its original hearers." "Students, pastors, Bible teachers and everyone who wants to understand Paul's message for the church will benefit from this resource."--BOOK JACKET.
Machine derived contents note: General Preface -- Author's Preface -- Introduction -- Outline of 1 Corinthians -- Commentary -- Bibliography.
Formerly CIP.
Includes bibliographical references (p. [325]-343)
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible; Bible. Corinthians, 1st - Commentaries; Commentaries